Еслиf( \frac{2x - 1}{3} ) = \frac{6x + 5}{3} то найдите значение f(1) - f(-2).​


Если то найдите значение f(1) - f(-2).​

lizagolovashko lizagolovashko    3   12.08.2020 16:13    0

Ответы
Shariknt Shariknt  15.10.2020 15:53

9

Пошаговое объяснение:

f (\tfrac{2x - 1}{3}) = \tfrac{6x + 5}{3} = \tfrac{6x - 3 + 8}{3} = 3 \cdot \tfrac{2 x - 1}{3} + \tfrac{8}{3} \Rightarrow f(x) = 3x + \tfrac{8}{3}

f(1) - f(-2) = 3 \cdot (1 - (-2)) = 3 \cdot (1 + 2) = 3 \cdot 3 = 9

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика